The arrangement - Day, Sylvia; Spencer, Minerva; Vayden, Kristin (Kensington Books, 2020)
MISCHIEF AND THE MARQUESS: Justin, the Marquess of Fontaine, and Lady Sophie Milton-Riley are completely ill-suited to one another. But they will have to prove it in order to end their mothers' insistence that they should marry. Yet the more they attempt to demonstrate how wrong their union would be, the more surprisingly, irresistibly right things feel.